Knowledge, Knowledge… Knowledge for My Economy - Richard B. Freeman (KDI Journal of Economic Policy, 2015)
The creation of S&T knowledge and development of S&T- based innovation has spread worldwide from traditionally advanced countries to traditionally developing countries, often under the direction of governments. Korea is an exemplar in this new locus. Korea's burst in Science and Technology during the last three decades has made Korea a substantive player in the global production of S&T knowledge and its application to business. Although Korea still trails the US and other top countries in the quality of research, it has leaped from its 1980s standing as bit player in the knowledge economy to being among the leaders in the early 21st Century. This paper shows that Korea's advance benefited from its active participation in the global market in higher education, in international research collaborations, and its close ties to the U.S. Korea's experience offers lessons for other countries who seek to advance by becoming knowledge economies. Korea proves that a developing country can gain comparative advantage in knowledge production and use; that government policy can stimulate such a development; and that openness to the world of higher education and research is the best way to move forward and overcome the middle income trap.
Keywords: I2; I23; J0; J24; O3; 330; Korea; Science and Technology; Education; R&D; Globalization